KONTINUITAS KARYA SASTRA JEPANG SEBAGAI PENYEMANGAT HIDUP MASYARAKAT JEPANG - Ida Ayu Laksmita Sari (Universitas Pendidikan Ganesha, 2013)
A good literary work is certainly timeless. When tsunami struck Japan, two poems and a song were continuously broadcasted on the television. The poems: Ame ni mo Makezu and Kodamadeshouka and the song: Ue o Muite Arukō were written long before the disaster. These works were able to motivate the Japanese people to unite and bounce back in facing the disaster. The author uses a liberal-humanist approach and literary sociology in analyzing the three factors. Based on the results, it is known that through liberal humanism the three literary works are indeed a good literary work since they have eternal significance. The repeated words are an emphasis that the Japanese people would not give up. While literary sociology reveals that when they were first written, these three works also served as a source of motivation to the people who were in the midsts of troubles. Since they were first written until today, especially when the tsunami struct, these three works continuously exist to motivate the Japanese people. Keywords: continuity, liberal humanism, literary sociology, tsunami